Estetika Macan Kurung sebagai Sumber Potensi Peningkatan Ekonomi Masyarakat dan Pelestarian Seni Ukir di Jepara - Habib Hasan Abdi Masabdi (Texture:Art and Culture Journal, 2023)
Regional culture is one of the things that become assets and is also used as an aspect of the identity of a community group that shows a form of manifestation of intellectual community. Art is one of the elements of culture that is the embodiment of the tastes of the nation's people related to beauty aspects or aesthetics. The city of Jepara is one of the cities in Central Java which is known to the world community as the City of Carving. Jepara’s carving art has developed over the centuries and this has positive impacts on the variety of creative designs and the quality of the sculptures. Jepara’s sculpture called "Macan Kurung" is one of the various types of carvings that are known by the wider community. The carving of the Macan Kurung statue has several elements that all create a coherent beauty. Macan Kurung can be studied through an aesthetic view and its meanings which are then analyzed for their relevance to the values of life in the present. The carving of the statue is not only used as an ornamental object that contains the values of life but can also be used as a source of income for the sculptor. Considering the production process of the sculpture has several complex stages and the carving technique is quite difficult and the quality is high, so it should be of added value for this sculpture carved product. With this added value, it is hoped that it will be able to improve the economy of the sculptor, which then becomes a separate motivation for the people of Jepara to develop their Carving Art. Although there is such great potential, on the other hand there are obstacles because the carving technique is quite difficult makes the regeneration of carving skills quite hampered. Coupled with the declining interest of the younger generation of Jepara in learning carving skills, this has an impact on the existence of the Art of Carving itself as the identity of the people of the Jepara city area.